Nosocomial infections in a Brazilian neonatal intensive care unit: a 4-year surveillance study - Brito,Denise Von Dollinger (2010)
INTRODUCTION: Report the incidence of nosocomial infections, causative microorganisms, risk factors associated with and antimicrobial susceptibility pattern in the NICU of the Uberlândia University Hospital. METHODS: Data were collected through the National Healthcare Safety Network surveillance from January 2006 to December 2009. The patients were followed five times/week from their birth to their discharge or death. RESULTS: The study included 1,443 patients, 209 of these developed NIs, totaling 293 NI episodes, principally bloodstream infections (203; 69.3%) and conjunctivitis (52; 17.7%). Device-associated infection rates were as follows: 17.3 primary bloodstream infections per 1,000 central line-days and 3.2 pneumonias per 1000 ventilator-days. The mortality rate in neonates with NI was 11.9%. Mechanical ventilation, total parenteral nutrition, orogastric tube, previous antibiotic therapy, use of CVC and birth weight of 751-1,000g appeared to be associated with a significantly higher risk of NI (p < 0.05). In multiple logistic regression analysis for NI, mechanical ventilation and the use of CVC were independent risk factors (p < 0.05). Coagulase- negative Staphylococcus (CoNS) (36.5%) and Staphylococcus aureus (23.6%) were the most common etiologic agents isolated from cultures. The incidences of oxacillin-resistant CoNS and S. aureus were 81.8% and 25.3%, respectively. CONCLUSIONS: Frequent surveillance was very important to evaluate the association of these well-known risk factors with NIs and causative organisms, assisting in drawing the attention of health care professionals to this potent cause of morbidity.